Food from Forest - Soni, Purshottam L. (Indian Forester, 1995)
After cellulose, starch is the most abundant carbohydrate obtained by photosynthesis. Starch is present in plant in the form of insoluble particles - the granules - and usually can be readily liberated from the plant tissues without degradation. Starch usually forms the chief source of carbohydrate in the human diet. At present, sources of starch are agricultural cereals, pulses and tubers. An account of twelve forest species - tubers and seeds - are given which shows forest could also be tapped for the commercial production of starch. Starch depending on the physico-chemical properties may be used in foodstuffs for improvement of their functional properties.